Mergers & Acquisitions and Their Impact on Corporate - Values: Pre and Post-Merger Analysis of Indian Banks - Verma, Bigyan Prakash; Maji, Pranab; Nair, Santosh (Indian Journal of Finance, 2013)
Primarily, the focus of the present study is on Mergers&Acquisitions, and how they have impacted Indian banks' corporate-values by analyzing both their pre&post-merger-performance. The period of the study ranged between the years 2000 and 2010. The researchers applied the techniques of Economic Value Added (EVA of Stern Stewart&Co.) to evaluate the performances of the chosen institutions in both the periods ( pre and post merger periods). The results signal towards the dynamism and resilience of the Indian economy. The researchers concluded that Indian banks, albeit small in comparison to their global counterparts, are taking great strides not only within the continental shelf of India, but even beyond its borders too.